2018
DOI: 10.1021/acs.jced.7b00748
|View full text |Cite
|
Sign up to set email alerts
|

Application of MOSCED To Predict Limiting Activity Coefficients, Hydration Free Energies, Henry’s Constants, Octanol/Water Partition Coefficients, and Isobaric Azeotropic Vapor–Liquid Equilibrium

Abstract: Modified Separation of Cohesive Energy Density (MOSCED) is a solubility parameter-based method to predict limiting activity coefficients. In addition to making quantitative predictions, MOSCED may additionally be used to understand the underlying molecular-level driving forces for intuitive solvent selection and formulation. A major improvement of MOSCED over similar solubility parameter methods is that it splits the association term. We show by example how this change allows MOSCED to better model the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 40 publications
(134 reference statements)
3
43
0
Order By: Relevance
“…Brouwer and Schuur [72] recently conducted a comparative study of eight predictive methods to compute ln γ ∞ i,j at 298.15 K. Of the methods evaluated, the solubility parameter method MOSCED was the top performer. This strong performance of MOSCED is consistent with the findings of the 2005 re-parameterization [20,73] and our recent work [8,74]. MOSCED was therefore selected as an additional comparison alongside UNIFAC.…”
Section: Reference Calculationssupporting
confidence: 82%
See 3 more Smart Citations
“…Brouwer and Schuur [72] recently conducted a comparative study of eight predictive methods to compute ln γ ∞ i,j at 298.15 K. Of the methods evaluated, the solubility parameter method MOSCED was the top performer. This strong performance of MOSCED is consistent with the findings of the 2005 re-parameterization [20,73] and our recent work [8,74]. MOSCED was therefore selected as an additional comparison alongside UNIFAC.…”
Section: Reference Calculationssupporting
confidence: 82%
“…The applications are vast for they are used in the design of separation equipment, solvent selection, the design of pharmaceuticals, stripping operations, leaching operations, and the extraction of dilute materials [2,3]. Previous studies have also shown that activity coefficients can be used to predict the formation of an azeotrope [4][5][6][7][8]. The equilibrium composition of a dilute mixture can be also be determined, thus having industrial applications in azeotropic distillation and high-purity extraction [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Techniques such as gas-liquid chromatography, 5,10 high-performance liquid chromatography 10 and differential ebulliometry 5,10,11 are traditionally used to measure activities in extremely dilute systems at varying concentrations, leading to the infinite dilution activity coefficient by extrapolation. 10 There has been considerable interest in predicting these coefficients [5][6][7][10][11][12][13][14][15][16][17][18][19][20][21] due to their use in phase equilibria studies in chemical engineering applications. [2][3][4]14 IDACs (also represented by γ ∞ ) are related to solvation free energies by the following equation: 6,7,13…”
Section: Introductionmentioning
confidence: 99%